The role of ‘Stage Theory of Bereavement,’ ‘Dual Process Model (DPM)’ and spirituality in dealing with grief during illness experience in cancer patients - Ismail, Shehenaz; Mohamad, Mardiana; Abdul Khaiyom, Jamilah Hanum; Dzulkifli, Mariam Adawiah (IIUM Press, International Islamic University Malaysia, 2023)
When individuals experience terminal illness based on their internalization of the illness, the construction of meaning and the adjustments made by the individual to accommodate changes that has occurred due to the illness, influences their cognitive and emotional representations based on the illness perception (Leventhal et al., 2001). The illness experience of some individuals leads them to experiences different types of losses and grief. According to Kubler Ross’ theory of loss and grief (2009), there are five stages of bereavement to cope with the grief experiences. Kubler Ross states that the individual goes through 5 stages of bereavement or grief while the Dual Process Model states the individual oscillates between the loss-oriented stressor and the restoration-oriented stressor. In addition, some researchers have found that spirituality is also a mechanism used to cope with loss and grief experiences. The aim of this paper is to examine an evaluate the theoretical frame works of The Dual Process Model of Coping with Bereavement (DPM) (Stroebe & Schut, 1999) the 5 Stages of Bereavement by Kubler Ross (Martin & Privette,1989), along with trying to understand the role of religion or spirituality to deal with loss and grief experiences among terminally ill patients such as patients with cancer.